Teachers’ Display and Referential Questions in Speaking Class: A Descriptive Study at UIN Ar-Raniry Banda Aceh (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2022)
Teachers’ questions play vipotal role in facilitating language learning by which the teachers often ask students to practice vocabulary, grammatical rules, or some expressions in the target language. Hence, this paper addresses types of questions explored by English lecturers in teaching speaking to English department students of UIN Ar-raniry Banda Aceh and investigate the most common type ocuured during the lesson. The data was collected through a recorded teaching session of Speaking class which then transcribed and analyzed by using Mile’s and Huberman’s (1992) model of data analysis consisting of data reduction, data display, and conclusion. The analysis revealed that the lecturer employed both display and refential questions to invite students’ speaking and engagement in the classroom. Further, referential questions is the the most frequent type of questions that occured in the classroom during the teaching and learning process. This study suggests that more referential questions can be maximized in language class to promote students’ speaking proficeincy and active learning.